Bone marrow osteoprogenitors are depleted whereas osteoblasts are expanded independent of the osteogenic vasculature in response to zoledronic acid. Issue 11 (6th September 2019) - Hughes, Russell; Chen, Xinyue; Hunter, Keith D.; Hobbs, Jamie K.; Holen, Ingunn; Brown, Nicola J.
Abstract : Zoledronic acid (ZOL) is an antiresorptive drug used to prevent bone loss in a variety of conditions, acting mainly through suppression of osteoclast activity. There is growing evidence that ZOL can also affect cells of the mesenchymal lineage in bone. We present novel data revealing significant changes in the abundance of perivascular mesenchymal stromal cells (MSCs)/osteoprogenitors and osteoblasts following the injection of ZOL, in vivo . In young mice with high bone turnover and an abundance of perivascular osteoprogenitors, ZOL significantly ( P < 0.0001) increased new bone formation. This was accompanied by a decline in osterix‐positive osteoprogenitors and a corresponding increase in osteoblasts. However, these effects were not observed in mature mice with low bone turnover. Interestingly, the ZOL‐induced changes in cells of the mesenchymal lineage occurred independently of effects on the osteogenic vasculature. Thus, we demonstrate that a single, clinically relevant dose of ZOL can induce new bone formation in microenvironments enriched for perivascular MSC/osteoprogenitors and high osteogenic potential. This arises from the differentiation of perivascular osterix‐positive MSC/osteoprogenitors into osteoblasts at sites that are innately osteogenic. Collectively, our data demonstrate that ZOL affects multiple cell types in bone and has differential effects depending on the level of bone turnover.—Hughes, R., Chen, X., Hunter, K. D., Hobbs, J. K., Holen, I., Brown, N. J. Bone marrow osteoprogenitors are depleted whereas osteoblasts are expanded independent of the osteogenic vasculature in response to zoledronic acid. FASEB J. 33, 12768–12779 (2019). www.fasebj.org